Key access and utilization descriptors for pearl millet genetic resources - Bioversity International; International Crops Research Institute for the Semi-Arid Tropics; United States Department of Agriculture; National Plant Germplasm System; All India Coordinated Research Project on Pearl Millet (2010)
This minimum list consists of an initial set of characterization and evaluation descriptors for pearl millet utilization.